A review of research on the Job Characteristics Model and the attendant job diagnostic survey - Billy Boonzaier; Bernhard Ficker; Braam Rust (South African Journal of Business Management, 2001)
The Job Characteristics Model is widely accepted as a conceptual tool for addressing problems related to employee demotivation, dissatisfaction and marginal performance. The validity of the Job Characteristics Model (Hackman Oldham, 1980) was assessed by reviewing relevant studies of the model. The review and evaluation is based on studies which test the variables and the relationships between variables as contained in the model. The evidence confirms that the dimensionality of the job characteristics is best represented by the five-factor solution as proposed by the model. The subjective self-report measures of the five job characteristics as formulated by the theory and measured by the revised Job Diagnostic Survey (JDS) are also supported. No evidence was found for the multiplicative Motivating Potential Score (MPS) and as a result the use of a simple additive index of job complexity is recommended as predictor of personal and work outcomes. Strong empirical support exists for the relationships between the job characteristics and the personal outcomes. Strong relationships between the job characteristics and the work outcomes, however, fail to materialize. Results fail to support the mediating effect of psychological states on the job characteristics/outcomes relationships as specified by the model. The postulated relationships between job characteristics and psychological states are also not confirmed by empirical evidence. The role of growth-need strength, knowledge and skill, and work environment characteristics as moderators of the relationships between job characteristics and psychological states, as well as the relationships between psychological states and personal and work outcomes, are seriously questioned. Directions for future research on the Job Characteristics Model and the attendant Job Diagnostic Survey are proposed.
Keywords: 650